The relationship between transformational leadership and work engagement among intensive care unit nurses: the mediating function of organizational climate - Lating Zhang; Lin Han; Xinhui Liang; Ruhua Wang; Haiyan Fan; Yao Jia; Sitong Li; Xue Jiang (BMC Nursing)
Abstract Background The high attrition rate and nursing shortage have a negative impact on the stability and advancement of the nursing business. For this reason, it is imperative to delve into the factors influencing nurses’ professional stability. Work engagement and transformational leadership are positively correlated with a decrease in nursing staff burnout. The aim of this study is to probe into the possible mediating function of organizational climate in this relationship. Methods In this cross-sectional study, 359 intensive care unit (ICU) nurses completed self-reported questionnaires to rate the transformational leadership and organizational climate in their workplaces and their work engagement. A structural equation model was developed to validate the associations among the variables. Results Transformational leadership, organizational climate and work engagement are all correlated. The relation between transformational leadership and work engagement is mediated by organizational climate. Conclusions The results indicate that organizational climate serves as an intermediary factor between transformational leadership and work engagement in ICU nursing staff. The study facilitates a deep understanding into the mechanism by which transformational leadership affects work engagement. This lends credence to the proposal that thorough intervention techniques for organizational climate need to be developed. Nursing managers need to prioritize transformational leadership and execute initiatives to improve organizational climate to elevate work engagement in nurses.